Dual Inversion Recovery Magnetic Resonance Imaging's Diagnostic Value for Estimating the Overall Load of Multiple Sclerosis Lesions and its Anatomical Distribution - Mohamed, Mahmoud Mishaal; Al-Ani, Maryam Issa; Al Gawwam, Gheyath; Alrubaye, Murtadha Hussein; Al-Imam , Ahmed Al-Imam (AL-Kindy College Medical Journal, 2024)
BBackground: In young adults, multiple sclerosis is a prevalent chronic inflammatory demyelinating condition. It is characterized by white matter affection, but many individuals also have significant gray matter involvement. A double inversion recovery pulse pattern was recently proposed to improve the detectability of multiple sclerosis lesions.Objectives: To evaluate the diagnostic value of double inversion recovery sequence in the detection of cortical and white matter multiple sclerosis plaques in different brain anatomical locations.Subjects and methods: A total of 37 patients with an established diagnosis of multiple sclerosis were included in this cross-sectional study. Brain MRI was done using double inversion recovery, T2 and FLAIR sequences. The number of lesions was counted and compared in the three sequences.Results: Dual Inversion Recovery sequence was highly significant and superior to both T2 and FLAIR sequences (P < 0.001) in depicting the lesions regardless of anatomical distribution. Dual Inversion Recovery was significantly superior to T2 (P =